Availability of agricultural credit: determinants, marginal effect, and predicted probability - Jisha K K; Prashobhan Palakkeel (Agricultural and Resource Economics, 2023)
Purpose. This paper aims to identify the major determinants of agricultural credit and their marginal effects, along with describing the pattern of the predicted probability of getting credit from the agricultural credit cooperatives.